Seniors as a research group in the experimental model - JAKUBOWSKA, LUBA (Journal of Education Culture and Society, 2020)
The article focuses on the conduct of experimental research with seniors. I would like to present the limitations and the advantages of experimental research in the following fi elds: specifi cs of the method, specifi cs of the research group and competences of the researcher. Data gathered through interviews with persons engaged in the experiment with seniors will serve as illustration of the discussion. In the article I have emphasised the limitations, but only in order to demonstrate how attempts can be made at dealing with them. The advan-tages connected with the opportunities provided by experimental research are self-evident.